EVALUASI TINGKAT KEBUGARAN JASMANI KLUB SEPAKBOLA SSB MENTARI SULHA KABUPATEN NAGAN RAYA - Masri Masri; Saiful Suryadi (Jurnal Dedikasi Pendidikan, 2020)
The level of physical fitness of Mentari Sulha Soccer SSB players can be said to be relatively low because in every championship game in the early minutes of the game they run well and fast, but in the second half until the end the physical condition decreases so that affects the game, this is marked by the body starting to appear tired to move and often missed and end up often losing. This study seeks to reveal the physical fitness level of SSB Mentari Sulha Football players. The purpose of the study was to obtain the level of physical fitness possessed by SSB Mentari Sulha Football players. The measurement approach is quantitative and qualitative. The population includes all SSB Mentari Sulha players with a sample of 16 players with a total sampling technique or saturated sample. Data collection using TKJI tests, namely running 50 and 1000 meters, hanging body lift, sitting lying down, jumping upright. Data analysis uses the average formula and frequency distribution. The results of data analysis showed that: 1) 1 player (6.25%) was in the "Good" category, 2) 8 players (50.00%) were in the "Medium" category, 3) 7 players (43, 75%) are in the "Poor" category. The conclusion of this study is that the physical fitness level of the SSB Mentari Sulha Soccer player in Nagan Raya Regency is Medium.